2016
DOI: 10.1002/ep.12450
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the leaching of heavy metals (Ni+2, Pb+2, Cr+3) contained in sludge waste stabilization/solidification by hydraulic benders, Part I: water/cement and waste/cement ratio in S/S mortars

Abstract: The aim of the present paper is to investigate the effect of the water/cement ratio (w/c) (0.4 and 0.6) and the amount of hazardous waste (W/c) (10, 20, 25, 30, and 45%) incorporated on the leaching of heavy metals from a cementitious solidified materials. Mechanical strength of the S/S materials was evaluated at 28 days of cure. Specimens that have shown a good mechanical strength for the two water/cement ratios were used to make this study succeed. XRD analysis has shown the presence of heavy metals within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…The release of the chlorides depends on the quantity of the waste added since the latter is contained just in the raw waste, the same result were found with the S/S mortars studied previously [23]. Calcium is contained in the metakaolin used for the synthesis of the geopolymer in small amount and in the waste with a large amount and, therefore, its release obviously depends on the amount of waste added.…”
Section: Leaching Testsupporting
confidence: 77%
See 2 more Smart Citations
“…The release of the chlorides depends on the quantity of the waste added since the latter is contained just in the raw waste, the same result were found with the S/S mortars studied previously [23]. Calcium is contained in the metakaolin used for the synthesis of the geopolymer in small amount and in the waste with a large amount and, therefore, its release obviously depends on the amount of waste added.…”
Section: Leaching Testsupporting
confidence: 77%
“…Average concentrations of heavy metals namely: Ni, Cr, and Pb are very large and far exceed the standards required by the regulations [34]. More information can be found in previous study [23]. All results obtained has shown that this waste is hazardous and must be stabilized before its disposal.…”
Section: Sludge Wastementioning
confidence: 93%
See 1 more Smart Citation
“…Freundlich equation is the description of multilayer, uniform, and heterogeneous adsorption of the adsorbate on the adsorbent. The Freundlich model is [34] q e 5K f C e 1=n (6) where K f is the adsorption capacity (mg/g) and 1/n is the adsorption intensity.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Numerous treatment methods, such as vitrification, acid extraction, adsorption, and solidification/stabilization (S/S), have been developed to prevent arsenic and heavy metal contamination . To date, S/S with ordinary Portland cement is the most common method for arsenic‐containing waste disposal .…”
Section: Introductionmentioning
confidence: 99%